Relationship between 5‐fluorouracil exposure and outcome in patients receiving continuous venous infusion with or without concomitant radiotherapy - Beneton, Maud; Chapet, Sophie; Blasco, Hélène; Giraudeau, Bruno; Boisdron‐Celle, Michèle; Deporte‐Fety, Régine; Denis, Fabrice; Narcisso, Bérangère; Calais, Gilles; Le Guellec, Chantal (British journal of clinical pharmacology, 2007)
What is already known about this subject • Dihydropyrimidine dehydrogenase (DPD) deficiency is currently evaluated as a means of identifying patients with a risk of toxicity during 5‐fluorouracil (5‐FU) treatment. • Therapeutic drug monitoring (TDM) is a complementary tool already shown to be useful for doses of 1000 mg m−2 day−1. • We carried out the first analysis of the concentration – effect relationships of 5‐FU administered at a dose of 600 mg m−2 day−1 with concomitant radiotherapy. What this study adds • No relationship was found between exposure and toxicity for 5‐FU administered at a dose of 600 mg m−2 day−1 with concomitant radiotherapy. • The use of TDM to improve tolerance to this treatment protocol is not supported by our data. • This study confirms the existence of an exposure – toxicity relationship for a dose of 1000 mg m−2 day−1 and has developed a simplified sampling strategy to make TDM easier to implement with this dose schedule. Aims Toxicity and response are correlated with plasma 5‐fluorouracil (5‐FU) concentration in patients treated with 5‐FU at a dose of 1000 mg m−2 day−1. Head and neck cancer patients are treated with various therapeutic regimens, including chemotherapy with 5‐FU at a dose of 600 mg m−2 day−1 with radiotherapy. We investigated the plasma concentration–effect relationship for this regimen, with the aim of developing recommendations for dose adjustment. Methods Patients received 5‐FU at doses of 600 or 1000 mg m−2 day−1, as a continuous infusion over 4 or 5 days, with or without radiotherapy for the 600 mg m−2 day−1 regimen. The area under the curve (AUC) for 5‐FU concentration was estimated, based on a single morning blood sample taken each day during treatment. AUC values were compared between patients with and without toxicity. This simplified method for AUC estimation was compared with the standard two‐samples‐per‐day method in an independent group of 50 patients. Results Forty‐six patients, corresponding to 115 courses, were included in this prospective study. Considerable interindividual variability in estimated AUC was observed for both doses. Grade 3–4 toxicity occurred in 10 and 21% of patients given doses of 600 and 1000 mg m−2 day−1, respectively. Ths study confirmed the relationship between plasma 5‐FU concentration and toxicity previously reported for 1000 mg m−2 day−1, but found no such relationship for the 600 mg m−2 day−1 regimen with concomitant radiotherapy. Conclusions Our results do not support the use of therapeutic drug monitoring to improve tolerance for the 600 mg m−2 day−1 regimen with concomitant radiotherapy. A simplified method is proposed for 5‐FU monitoring for the 1000 mg m−2 day−1 regimen.